2020
DOI: 10.17085/apm.20065
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography for lumbar neuraxial block

Abstract: Ultrasonography can be useful to perform a lumbar neuraxial block. It aids in understanding the anatomy of the lumbar spine before the procedure. Pre-procedural ultrasound imaging provides information about the accurate intervertebral level for puncture, optimal needle insertion point, and depth of needle advancement for a successful neuraxial block. The key ultrasonographic views for lumbar neuraxial block include the transverse midline interlaminar and parasagittal oblique views. Ultrasonography can facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Once an approach is decided, the needle insertion site can be determined. Palpation has traditionally been used to identify anatomical landmarks that facilitate proper insertion; however, ultrasound guidance is becoming more frequently used to directly visualize intervertebral spaces and the associated needle insertion point, depth, and angle in real-time preprocedural ( 36 ). While some studies have shown superior accuracy or ease of needle placement assisted by newer techniques involving ultrasound, it remains controversial as others have shown no clear advantage ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Once an approach is decided, the needle insertion site can be determined. Palpation has traditionally been used to identify anatomical landmarks that facilitate proper insertion; however, ultrasound guidance is becoming more frequently used to directly visualize intervertebral spaces and the associated needle insertion point, depth, and angle in real-time preprocedural ( 36 ). While some studies have shown superior accuracy or ease of needle placement assisted by newer techniques involving ultrasound, it remains controversial as others have shown no clear advantage ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that ultrasonography can help with spinal anesthesia in patients with difficult anatomy such as severe obesity, lumbar scoliosis, ankylosing spondylitis, and post-lumbar spine surgery. [ 7 ] However, there have been few reports on the anatomical changes in lumbar subcutaneous fat, and no reports were found of these changes being noted on pre-procedure ultrasonography. We call this structure the back fat slope.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is even more helpful when applied in those cases with anticipated difficulty, including anatomical alteration of the lumbar spine and a body mass index (BMI) > 33 kg/m 2 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%